Natural flavonoids: Potential therapeutic strategies for non-alcoholic fatty liver disease - Tan, Panli; Jin, Li; Qin, Xiang; He, Beihui (Frontiers in Pharmacology, 2022)
The incidence of non-alcoholic fatty liver disease (NAFLD) is increasing rapidly worldwide; however, there are currently limited treatments for NAFLD. The disease spectrum includes simple fatty liver, non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and progression to hepatocellular carcinoma (NASH-HCC). The therapeutic effects of NAFLD remain controversial. Although researchers have conducted studies on the pathogenesis of NAFLD, its pathogenesis and anti-NAFLD mechanisms have not been fully elucidated. Previous studies have found that flavonoids, as natural substances with extensive pharmacological activity and good therapeutic effects, have excellent antioxidant, anti-inflammatory, metabolic disease improvement, anti-tumor, and other properties and can significantly alleviate NAFLD. Flavonoids could be further developed as therapeutic drugs for NAFLD. In this paper, the pathogenesis of NAFLD and the mechanisms of flavonoids against NAFLD are summarized to provide a theoretical basis for screening flavonoids against non-alcoholic liver injury.